Advancing Sustainable Economies Through Green Banking: A Systematic Review - Dewi, Nike Silvia; Gunawan, Veronica Christin; Indriani, Farida (LifeSciFi, 2024)
Global attention is now beginning to focus on environmental protection given the increasing rate of global warming. This study aims to examine the practice of green banking where its execution can help in accomplishing the goal of sustainable development and economic sustainability. This study analyzes the role of banking in the implementation of green banking in terms of financing, assortment of green banking products and reporting. Green banking innovation in the banking industry means balancing economic success with social and environmental responsibility. This research utilizes a systematic literature review related to green banking and its link to economic sustainability that includes articles published from 2018 to 2024 to ensure the findings are relevant. The results of this study are expected to affirm the importance of green banking practices in connection to making economic sustainability and contribute to raising awareness of the importance of observing the environmental impacts of bank financing.